K-12 teachers’ perceptions of the effectiveness of online EFL teaching and learning during the COVID-19 pandemic - Zou Bin; Chen Xinyi; Sun Weifeng (Journal of China Computer-Assisted Language Learning)
During the Coronavirus disease outbreak, education in schools and universities was conducted through online platforms worldwide. School teachers in China have had a taste of online teaching, which never appeared to be a necessity before the COVID-19 pandemic in 2020. This research explores the effectiveness of English as a foreign language (EFL) teaching at the primary and secondary school levels during the COVID-19 pandemic in China. The research tools comprise questionnaires and semi-structured interviews. A total of 132 teachers from more than 10 provinces completed the online questionnaire, and 12 teachers were involved in semi-structured interviews. The results showed that while some EFL teachers adopted effective online pedagogies, others encountered challenges in online teaching. The teachers who had comprehensive Technological Pedagogical Content Knowledge (TPACK) or with previous online teaching experience tended to be more optimistic about teaching effectiveness in online language education. However, less training and a lack of TPACK and skills can hinder effective online teaching.